Grupo interdisciplinar: Construção de unidade educacional sistematizada em aprendizagem baseada em problemas - Tanaka, Ioshie Ibara [UNESP]; Da Rocha Tonhom, Sílvia Franco; De Fatima Taipeiro, Elane; Guimarães, Ana Paula Ceolotto; De Aguiar Dutra Moravcik, Maria Yvette; Sartori, Teresa Cristina França [UNESP]; Takeda, Elizabete (My University, 2013)
In 2003 the construction team of the 1st grade of the medical and nursing courses from a medical school began a work aiming at curriculum reconstruction, and restructured cognitive contents and the integration of basic and clinical aspects, in order to adapt to the incentive program for Curriculum Changes (PROMED) which allows for the continuity of curricular innovations. This team worked considering the group dynamics, a method already used in tutorial sessions which teachers have some familiarity with. For a good group performance the team participants were divided into two subgroups: one for constructing educational problems and the other for doing cognitive assessment exercises. The team and the subgroups met weekly, and every 15 days the group met for socialization of information, identifying the strengths and weaknesses of the process and/or products. A good adhesion, an active involvement of participants and satisfaction expressed by each participant with their inclusion in the group were reflected in the final product and contributed to the subjects' commitment to the proposal. This way, in the process the individual transformations and relations in a situation requiring the collaboration of professionals were essential in the process of permanent curricular reconstruction.
Interdisciplinary group: Construction of a systematized educational unit based on problem-based learning
Keywords: Health education; Interdisciplinary studies; Patient care team; Problem-based learning